Analysis of Learning Media In The Holistic Curriculum of IPAS Subjects at SD Negeri 35 Kimindores, Southwest Papua - Harni, Harlina; Rosidah, Cholifah Tur; Rosmiati (Program Studi Tadris IPA, Fakultas Tarbiyah (IAIN) Kediri, Indonesia, 2024)
This study aims to analyze the use of learning media in learning Natural and Social Sciences (IPAS) at SD Negeri 35 Kimindores, Southwest Papua. This research uses a qualitative approach to gain an in- depth understanding of the effectiveness of learning media, student responses, and the characteristics of learning media in the context of the Holistic Curriculum. Data were collected through observation, interviews with teachers and students, and document analysis related to the learning media used. The results showed that the learning media used at SD Negeri 35 Kimindores in Southwest Papua are diverse, including visual, audio, manipulative, and digital media. Students show high enthusiasm for the use of learning media and find it useful in understanding the concept of IPAS. However, some media are less integrated with the principles of the Holistic Curriculum, such as the lack of focus on developing critical, collaborative and creative thinking skills. This research provides important implications for the development of learning media that are more effective and in accordance with the principles of the Holistic Curriculum.